ACCOUNTING OF ZAKAT, INFAK AND ALMS IN TRANSPARENCY AND ACCOUNTABILITY IN LAZ DOMPET AMANAH UMAT SIDOARJO - Ramadhani Suci Restuningtyas; Anna Marina; Fitri Nuraini (UMSurabaya Publishing, 2017)
ABSTRACT The potential magnitude of zakat fund receipts must be balanced with good management. The development of Badan Amil Zakat (BAZ) and Lembaga Amil Zakat (LAZ) in Indonesia needs to be followed by a good and transparent public accountability process by prioritizing the motivation to carry out the mandate of the people. In order for zakat management to work properly, BAZ/LAZ must apply the principles of Good Organization Governance. This study aims to find out the comparison of the application Accounting of Zakat and Infak/Alms to LAZ Dompet Amanah Umat (LAZ DAU) with PSAK No. 109 in transparency and accountability. The research approach used qualitative descriptive with comparative method. The results revealed that the application accounting of zakat and infak/alms LAZ DAU is sufficient in accordance with PSAK No. 109 in the case of recognition of funds received and distributed in cash, non-cash fund measurement, zakat fund disbursement, infak/alms and amil separately, and disclosure of non-halal funds. The principles of transparency and accountability are realized by publishing reports on receipts, expenditures and cash/bank balances, conducting audits of the External Auditor as well as the preparation of program accountability reports. The principle of transparency has not been fully implemented because the transaction of non-refundable receipt and distribution of funds is not done. Suggestion given in order to apply accounting of zakat and infak/alms in accordance with PSAK No. 109, establishes policies on limits of small cash usage as well as prepares and publishes complete financial statements.Keywords : Accounting of Zakat and Infak/Alms, Transparency, AccountabilityCorrespondence to : ramadhanisucirestuningtyas@gmail.com ABSTRAK Besarnya potensi penerimaan dana zakat harus diimbangi dengan pengelolaan yang baik. Perkembangan Badan Amil Zakat (BAZ) dan Lembaga Amil Zakat (LAZ) di Indonesia perlu diikuti dengan proses akuntabilitas publik yang baik dan transparan dengan mengedepankan motivasi melaksanakan amanah umat. Agar pengelolaan zakat berjalan dengan baik, maka BAZ/LAZ harus menerapkan prinsip-prinsip Good Organization Governance. Penelitian ini bertujuan untuk mengetahui perbandingan penerapan Akuntansi Zakat dan Infak/Sedekah pada LAZ Dompet Amanah Umat (LAZ DAU) dengan PSAK No. 109 dalam transparansi dan akuntabilitas. Pendekatan penelitian yang digunakan kualitatif deskriptif dengan metode komparatif. Hasil penelitian mengungkapkan bahwa penerapan akuntansi zakat dan infak/sedekah LAZ DAU sudah cukup sesuai dengan PSAK No. 109 dalam hal pengakuan dana yang diterima dan disalurkan dalam bentuk kas, pengukuran dana nonkas, penyajian dana zakat, infak/sedekah, dan amil secara terpisah, serta pengungkapan dana non halal. Prinsip transparansi dan akuntabilitas diwujudkan dengan mempublikasikan laporan penerimaan, pengeluaran dan saldo kas/bank, dilakukannya pemeriksaan Auditor Eksternal serta disusunnya laporan pertanggungjawaban program. Prinsip transparansi belum sepenuhnya diterapkan karena transaksi penerimaan dan penyaluran dana nonkas tidak dilakukan pencatatan. Saran yang diberikan agar dapat menerapkan akuntansi zakat dan infak/sedekah sesuai dengan PSAK No. 109, membuat kebijakan atas batas penggunaan kas kecil serta menyusun dan mempublikasikan laporan keuangan secara lengkap.Kata Kunci : Akuntansi Zakat dan Infak/Sedekah, Transparansi, AkuntabilitasKorespondensi : ramadhanisucirestuningtyas@gmail.com